Specific Aspects of the Principle of Humanitarianism in Ensuring the Needs and Interests of Young People - Yuldashev Farrux Abdurakhmanovich, Phd; Yuldasheva Nigora Bakhodirovna (Genius Journals, 2023)
This article discusses the role and place of the ideals of humanism as well as tolerance in the development of ethics, culture, humanistic qualities of young people who are the leading forces of our society. There are ideas about the wide use of the scientific heritage of the scientists and thinkers in the life of youth.
Keywords: Purpose; need; interest; stability